2018
DOI: 10.1177/0163443718798898
|View full text |Cite
|
Sign up to set email alerts
|

The need for not more, but more socially relevant audience participation in public service media

Abstract: In public service media (PSM) theory and policy, it is argued that more audience participation is needed in the production of PSM programs. However, little research has been done on the actual implementation and evaluation of audience participation in practice. Therefore, we investigate the values and meanings media users attach to participatory opportunities in PSM. We focus on the case of Bel10, a radio project of the Flemish public broadcaster VRT, as audience participation in radio is an underresearched fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 14 publications
0
9
0
2
Order By: Relevance
“…On a related point, we can point to the ample amount of research available that offers insights into the employment of participating features on news websites. The findings reported from such projects can largely be understood along three dimensions: newsroom perceptions of audience access and participation (e.g., Domingo et al, 2008; Lawrence et al, 2017; Lie, 2018; Morlandstø & Mathisen, 2016; Scott et al, 2015; Stroud et al, 2016), the role of social plugins in news websites (e.g., Givskov & Trenz, 2014; Manosevitch & Tenenboim, 2016; Wikström & Ellonen, 2012) and the actual use and appreciation of such services in relation to online news media (e.g., Almgren & Olsson, 2016; Bobkowski et al, 2019; Borger et al, 2016; Kalsnes & Larsson, 2018; Krumsvik, 2018; Larsson, 2011; Meijer & Kormelink, 2015; Spyridou, 2018; Vanhaeght, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…On a related point, we can point to the ample amount of research available that offers insights into the employment of participating features on news websites. The findings reported from such projects can largely be understood along three dimensions: newsroom perceptions of audience access and participation (e.g., Domingo et al, 2008; Lawrence et al, 2017; Lie, 2018; Morlandstø & Mathisen, 2016; Scott et al, 2015; Stroud et al, 2016), the role of social plugins in news websites (e.g., Givskov & Trenz, 2014; Manosevitch & Tenenboim, 2016; Wikström & Ellonen, 2012) and the actual use and appreciation of such services in relation to online news media (e.g., Almgren & Olsson, 2016; Bobkowski et al, 2019; Borger et al, 2016; Kalsnes & Larsson, 2018; Krumsvik, 2018; Larsson, 2011; Meijer & Kormelink, 2015; Spyridou, 2018; Vanhaeght, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…From the perspective of participants, few studies actually provide empirical evidence that supports the oft-repeated argument that news is increasingly becoming a social experience—and that “people en masse actively [want to] contribute to news through sharing, recommending etc.” (Meijer & Kormelink, 2015, p. 675). The often reported low levels of use of interactive features could be seen as suggesting that it takes time for users to adapt to these new opportunities (Larsson, 2011), that audiences are shy, lazy, and fearful about expressing themselves to each other (Hujanen & Pietikäinen, 2004; Spyridou, 2018) or simply that they do not have the urge to participate in media production (Kalogeropoulos et al, 2017; Krumsvik, 2018; Vanhaeght, 2018). In terms of sharing, Bobkowski et al (2019) found that one in three respondents use social media to share news articles, while three in four share news stories by discussing them with friends and family.…”
Section: Literature Reviewmentioning
confidence: 99%
“…More recent research on the Belgian participatory radio program Bel10 demonstrated related results. 40 In this study, media users especially appreciated participatory opportunities on the radio when they visibly contributed to the diversity, authenticity and critical quality of radio content. In other words, they valued audience input when it helped place critical topics on the policy agenda.…”
Section: F R O M M E D I a -C E N T R I C T O S O C I E T Y -C E N T mentioning
confidence: 88%
“…They are against increasing participation for its own sake, without assessing the deliberative quality and enhancing the forms of participation. Exemplary in a media context, is the critique on the use of vox pops as a poor-quality form of audience participation (Vanhaeght, 2019). In these short street interviews, the conditions for participations are far from ideal, as the man in the street is often too overwhelmed and does not get any room to think.…”
Section: More Participation the Better?mentioning
confidence: 99%